2018
DOI: 10.1016/j.geotexmem.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic gradient ratio test apparatus

Abstract: The soil-geotextile filtration mechanism is a complex process which depends on physical compatibility between the geotextile and the soil to be retained. Several methods have been proposed by researchers for assessing the filtration behaviour of soil-geotextile composite systems under steady state conditions. The Gradient Ratio (GR) test is the most commonly used method for measuring filtration compatibility of soil-geotextile systems. This paper describes the design of a modified GR permeability test apparatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Very little research has been done to assess the filtration performance of geotextiles under highways and railways (Bell et al, 1982;Hoare, 1982;Alobaidi and Hoare, 1996, Fatahi et al, 2011, Kermani et al, 2018. Apparatus used to test filters have lacked control over stresses as well as precision of measurements (Khan et al, 2018). In addition, the internal stability of soils has not been taken into account.…”
Section: (B)) a F-hmentioning
confidence: 99%
See 1 more Smart Citation
“…Very little research has been done to assess the filtration performance of geotextiles under highways and railways (Bell et al, 1982;Hoare, 1982;Alobaidi and Hoare, 1996, Fatahi et al, 2011, Kermani et al, 2018. Apparatus used to test filters have lacked control over stresses as well as precision of measurements (Khan et al, 2018). In addition, the internal stability of soils has not been taken into account.…”
Section: (B)) a F-hmentioning
confidence: 99%
“…Test specimens were prepared in a dynamic GR apparatus (Khan et al (2018); see Fig. 4) which can accommodate samples 50mm in diameter and 100mm high.…”
Section: Specimen Preparationmentioning
confidence: 99%
“…Dry and wet sieving, hydrodynamic sieving, mercury intrusion porosimetry, image analysis, and bubble point methods are commonly used to evaluate the pore size distribution of geotextiles (Aydilek et al 2002;Bhatia & Smith 1996); the different methods used to define soil and geotextile filtration, retention, and clogging criteria have also been studied earlier (Bhatia & Huang 1995;Faure et al 2006;Ghataora et al 2006;Ghosh & Yasuhara 2004;Palmeira et al 1997;Palmeira 2009;Xiao & Reddi 2000). The Gradient Ratio (GR) and Hydraulic Conductivity Ratio (HCR) are the common methods used to determine the permeability, hydraulic conductivity, and filtration capacity of geotextiles (Khan et al 2018;Palmeira & Gardoni 2000;Williams & Abouzakhm 1989). To evaluate the filtration of soil geotextile systems, the GR method is mainly used to describe the relationship between the hydraulic gradient across the soil geotextile interface and the hydraulic gradient that develops within the soil.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, fibrous filter materials have gradually replaced traditional granular filters due to their advantages of easy installation, space savings, and the versatility achieved through variations in fabric design/manufacture. [8][9][10] In the filtration process, filter performance is influenced by various parameters, including the physical properties of the soil (the particle type, concentration and size distribution) and the structural parameters of the fibrous filter (manufacturing process, opening size and thickness). 11,12 Koerner and Koerner 13 found that nonwoven geotextiles were easily clogged in cohesionless fine-grained soils based on a survey of 69 field failures involving geotextile filters.…”
mentioning
confidence: 99%